2020
DOI: 10.1016/j.jped.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal COVID-19: little evidence and the need for more information

Abstract: Based on available reports (up to the writing of this editorial) and on scientific data reported by China, Italy, and the United States, newborn infants appear to be significantly less affected by COVID-19 than adults. 1---3 However, the lack of high-quality evidence for this situation and the steadfast pace of new and conflicting information has been an overall challenge to all medical specialties, including neonatal intensive care. In reality, the current knowledge on neonatal severe acute respiratory syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
(10 reference statements)
0
5
0
20
Order By: Relevance
“…Por meio dos estudos analisados, percebe-se que alguns casos de COVID-19 positivos, foram relatados no Brasil por meio do noticiário ou de apresentações clínicas (Procianoy, et al, 2020), o que reforça que a vigilância deve ser mantida nesta população.…”
Section: Discussionunclassified
“…Por meio dos estudos analisados, percebe-se que alguns casos de COVID-19 positivos, foram relatados no Brasil por meio do noticiário ou de apresentações clínicas (Procianoy, et al, 2020), o que reforça que a vigilância deve ser mantida nesta população.…”
Section: Discussionunclassified
“…Hence, it is advisable to use the appropriate size filter for newborn infants and avoid prolonged ventilation using this approach, especially in the smaller, extremely preterm infants. 12,13 It is also unclear if the addition of a filter could affect ventilatory technique especially during mask ventilation. The extra weight of the filter may impair effective mask ventilation technique leading to increased leak.…”
Section: Particle Filtermentioning
confidence: 99%
“…There is insufficient evidence behind the airflow dispersion pattern and transmission risk to HCWs when performing AGMPs during neonatal resuscitation or stabilization. 12,13 It is postulated that aerosolization during AGMPs in neonatal resuscitation is much lower than that of an adult due to the lower tidal volumes with dispersion distances of <2 cm estimated. 6,12 However, there are no neonatal data to support this and it is difficult to extrapolate the limited adult data 14 into neonatal settings.…”
Section: Introductionmentioning
confidence: 99%
“…In a digital study of a baby born to a mother with COVID-19, 2 hours after birth, the baby's antibodies and cytokines levels were abnormal. Given that IgM antibodies were not transmitted to the fetus through the placenta, the IgM levels indicated that the baby was infected in the womb [22,23] .…”
Section: Vertical Transmission Of Covid-19 Virus From Pregnant Mother To Infantmentioning
confidence: 99%